Development of prototype gold nanoparticle-dased immunoassays for the detection of plasmodium falciparum hsp70 - Guirgis, Bassem Samy (AUC Knowledge Fountain, 2011)
Biomedical nanotechnology is providing revolutionary opportunities for the rapid and simple diagnosis of many infectious diseases. About half of the world's population are at risk of infection with malaria and diagnostic assays available either lack sensitivity and specificity or require expensive equipment, expertise or costly infrastructure; that are not usually available in countries where the disease is endemic. Thus, there is an urgent need to develop rapid, sensitive, and inexpensive diagnostic tests for malaria for both high- and low-resource settings. In this study, we developed two prototype gold nanoparticle (AuNP)-based immunoassays for the detection of Plasmodium falciparum Heat Shock Protein 70 (PfHsp70) antigen. PfHsp70 is a heat shock protein that has recently attracted attention as a novel therapeutic target. Monoclonal antibody (2E6) against PfHsp70 was produced and purified using immunoaffinity chromatography. Proof-of-concept for using Hsp70 as a diagnostic target was carried out by comparing the pellet of saponin-treated red blood cells of infected mice with that of non-infected mice or healthy humans, by Western blot. His-tagged-PfHsp70 antigen was expressed from a genetically modified E. coli system and purified by affinity chromatography. For the development of the immunoassays, conjugation of mercaptoundecanoic acid (MUA) capped AuNPs with 2E6 was performed in presence and absence of protein cross-linkers. Characterization of the obtained bio-nanoconjugate (BNC) was performed using UV-visible spectrophotometry, agarose gel electrophoresis and Î¶-potential measurements. Stability of the BNC against high salt concentrations and pH changes was also assessed. Based on the described antibody/antigen system, two prototype immuno-competitive assays were developed in two distinct formats, namely, (i) a colorimetric chip assay, and (ii) a fluorescent quenching competitive assay. Proof-of-concept of chip assay allowed the comparison between conjugates prepared with and without NHS/EDC and it was found that non-NHS/EDC conjugates were more active. A fluorescence quenching competitive prototype assay was also developed which had a limit of detection of 87 ng/mL (1.16 pM). As Hsp70 is a rather ubiquitous protein, other Plasmodium specific proteins that are secreted into the plasma of malaria patients will be identified in the future in the search of new diagnostic targets. Also further developments of the fluorescence quenching competitive assay will involve the use of cubical and decahedral AuNPs in order to try to increase the sensitivity of the assay as compared to spherical AuNPs.